2004
DOI: 10.1182/blood-2003-05-1425
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of respiratory syncytial virus infection in cancer and transplant patients: implications for management

Abstract: Respiratory syncytial virus (RSV) has been reported to cause severe morbidity and mortality among cancer patients receiving chemotherapy with or without autologous peripheral blood stem cell transplantation (APBSCT). However, little is known about the natural history of this infection in these patients, and current standard practice, aerosolized ribavirin plus intravenous immunoglobulin (IVIG), is extremely expensive, difficult to use, and not supported by controlled clinical trials. The purpose of this observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 50 publications
1
45
1
Order By: Relevance
“…Although RSV has been associated with fatal pneumonia without evidence of superinfections by other pathogens, 10 other groups have provided evidence that RSV positivity in immunocompromised patients was not associated with any adverse outcome. 7,8 It is indeed difficult to assess to what extent the fatal outcome could be attributed to the RSV infection in our cohort, because this particular population typically suffers from several comorbidities and co-infections. The fatal cases in the outbreak described here showed that the majority (11/14 patients) had co-infections with other viral (BK virus, CMV, EBV, Herpes simplex virus-in one case acyclovir resistant), bacterial (for example, multi-drug resistant Pseudomonas aeruginosa) or fungal (Aspergillus fumigatus) pathogens.…”
Section: Rsv Infections In Hematology and Transplant Unit N Lehners Ementioning
confidence: 99%
See 1 more Smart Citation
“…Although RSV has been associated with fatal pneumonia without evidence of superinfections by other pathogens, 10 other groups have provided evidence that RSV positivity in immunocompromised patients was not associated with any adverse outcome. 7,8 It is indeed difficult to assess to what extent the fatal outcome could be attributed to the RSV infection in our cohort, because this particular population typically suffers from several comorbidities and co-infections. The fatal cases in the outbreak described here showed that the majority (11/14 patients) had co-infections with other viral (BK virus, CMV, EBV, Herpes simplex virus-in one case acyclovir resistant), bacterial (for example, multi-drug resistant Pseudomonas aeruginosa) or fungal (Aspergillus fumigatus) pathogens.…”
Section: Rsv Infections In Hematology and Transplant Unit N Lehners Ementioning
confidence: 99%
“…3 Although RSV is usually a self-limiting disease causing only mild symptoms of upper respiratory tract infection disease (URTID) or no symptoms at all, 4 it may be associated with severe LRTID in elderly or immunocompromised adults. 5,6 Morbidity and mortality rates reported in the literature are heterogeneous, the relevance of RSV infections in terms of outcome for patients undergoing autologous or allogeneic SCT ranging from none 7,8 to a mortality rate of up to 78%. [9][10][11][12][13][14] The impact of RSV on fatal outcome in this often multimorbid patient population might be difficult, if not impossible, to assess.…”
Section: Introductionmentioning
confidence: 99%
“…or oral applications, but no controlled clinical trials to reach treatment consensus have been conducted. 6,13 Aerosolized ribavirin has been the most frequently used treatment for RSV after HSCT. 10 Its use has been limited on account of the lack of proven efficacy and potential toxicity to caregivers exposed to the drug, including potential teratogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…No RSV-specific gamma globulin or humanized MoAb (palivizumab) was administered. All four LRTI patients showed a favorable clinical response, with 100% survival after a mean follow-up of 17 months (range [13][14][15][16][17][18][19][20][21][22][23][24]. With regard to IVIG, our guideline was not adhered to in two patients with severe LRTI-RSV who did not receive combined therapy with IVIG (episodes 1 and 6).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…A more severe clinical course has been associated with early occurrence post-transplantation, chronic GVHD, persistant lymphopenia and allogeneic HSCT. [1][2][3][4][5][6][7][8] As preemptive therapy and treatment with aerosolized ribavirin and anti-RSV antibodies offer only modest benefits 1,[8][9][10][11][12][13][14] and no effective vaccine is currently available, recent strategies have focused on RSV infection prevention.…”
Section: Introductionmentioning
confidence: 99%